Inhibition of PAK1 suppresses pancreatic cancer by stimulation of anti-tumour immunity through down-regulation of PD-L1. (1st March 2020) - Wang, Kai; Zhan, Yifan; Huynh, Nhi; Dumesny, Chelsea; Wang, Xiao; Asadi, Khashayer; Herrmann, David; Timpson, Paul; Yang, Yang; Walsh, Katrina; Baldwin, Graham S.; Nikfarjam, Mehrdad; et al.
Abstract: Immunotherapies have not yielded significant clinical benefits for pancreatic ductal adenocarcinoma (PDA) because of the existence of an immunosuppressive tumour microenvironment (TME) characterized by a desmoplastic stroma containing infiltrated immune cells and activated pancreatic stellate cells (PSCs). This study aims to investigate the involvement of PAK1 in anti-tumour immunity. In PDA patients, low PAK1 expression, low activation of PSC and high CD8 + T cell/PAK1 ratios correlated with longer overall survival. In a murine PDA model, PAK1 knockout increased intra-tumoral CD4 + and CD8 + T cells, inhibited PSCs activation and extended survival. Inhibition of PAK1 reduced PSC-stimulated PDA cell proliferation and migration, blocked PSC-mediated protection of PDA cells from killing by cytotoxic lymphocytes and decreased intrinsic and PSC-stimulated PD-L1 expression in PDA cells, which further sensitized PDA cells to cytotoxic lymphocytes. Inhibition of PAK1 stimulates anti-tumour immunity by increasing intra-tumoral CD4 + and CD8 + T cells, and by sensitizing PDA cells to killing by cytotoxic lymphocytes via down-regulation of intrinsic and PSC-stimulated PD-L1 expression. PAK1 inhibitors, especially in combination with immune checkpoint inhibitors may result in improved efficacy of immunotherapy of PDA. Highlights: Low PAK1 expression is related to reduced tumour growth and better survival. PAK1 regulates the activity of pancreatic stroma and tumour immune response. Deletion of PAK1 decreases PSC-stimulated PDA cell proliferation and migration. PAK1 inhibition reduces intrinsic and PSC-stimulated PD-L1 expression in PDA cells. Inhibition of PAK1 enhances cytotoxic lymphocyte-induced PDA cell death.